2013
DOI: 10.1017/s1049023x13003476
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-Resistant Staphylococcus Aureus Nasal Colonization Prevalence among Emergency Medical Services Personnel

Abstract: There is evidence that EMS personnel have a higher prevalence of MRSA colonization than the general population. This can be a risk to patients and can be recognized as an occupational hazard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…the potential for the existence of MRSA in emergency service helicopters is very real. This is particularly likely given that the prevalence of MRSA among emergency services personnel is reported to be over four times that of the general population [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the potential for the existence of MRSA in emergency service helicopters is very real. This is particularly likely given that the prevalence of MRSA among emergency services personnel is reported to be over four times that of the general population [14].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has demonstrated a high prevalence of MRSA among emergency services personnel (6.4%) compared to 1.5% in the general population [14]. Furthermore, previous studies have found MRSA in ambulances in both metropolitan (47.6%) [15] and rural areas (49%) [16].…”
Section: Introductionmentioning
confidence: 97%
“…Surveillance systems for infectious diseases, in the realm of disaster preparedness, will help to monitor new biological incidents as soon as they occur, and will help protecting EMS personnel as first line responders to such events [12] . Al Amiry suggested that CA-MRSA can be viewed as an occupational hazard at a prehospital setting level and to further protect EMS personnel with proper guidelines that deal effectively with MRSA community outbreaks, as well as other outbreaks that may threaten humanity at large [12] .…”
Section: In Preparation For Bioterrorismmentioning
confidence: 99%
“…Al Amiry suggested that CA-MRSA can be viewed as an occupational hazard at a prehospital setting level and to further protect EMS personnel with proper guidelines that deal effectively with MRSA community outbreaks, as well as other outbreaks that may threaten humanity at large [12] .…”
Section: In Preparation For Bioterrorismmentioning
confidence: 99%
See 1 more Smart Citation